Experimental and theoretical simulations of seismic poundings between two adjacent structures. - Chau, K.T (Earthquake engineering & structural dynamics.)
Shaking table tests have been carried out to investigate the pounding phenomenon between two steel towers of different natural frequencies and damping ratios, subject to different combinations of stand off distance and seismic excitations. Both harmonic waves and ground motions of the 1940 El Centro earthquake are used as input. Subjected to sinusoidal excitations, poundings between the two towers could appear as either periodic or chaotic. For periodic poundings, impact normally occurs once within each excitation cycle or within every other excitation cycle. A type of periodic group poundings was also observed for the first time (i.e. a group of non periodic poundings repeating themselves periodically). Chaotic motions develop when the difference of the natural frequency of the two towers become larger. Under sinusoidal excitations, the maximum relative impact velocity always develops at an excitation frequency between the natural frequencies of the two towers. Both analytical and numerical predictions of the relative impact velocity, the maximum stand off distance, and the excitation frequency range for pounding occurences were made and found to be comparable with the experimental observations in most of the cases. The stand off distance attains a maximum when the excitation frequency is close to that of the more flexible tower. Pounding appears to amplify the response of the stiffer structure but suppress that of the more flexible structure; and this agrees qualitatively with previous shaking table tests and theoretical studies.